Strategi Partisipatif Pembangunan Sosial di Pulau Penyengat Kota Tanjungpinang - Mahadiansar Mahadiansar; Fedro Romadhan (Civitas Consecratio: Journal of Community Service and Empowerment, 2021)
Social development is part of the strategy in mobilizing community participation so that the sustainable development sector can have a role with the presence of a participatory community. This paper describes the current conditions that occur on the island of Penyengat as a strategic area in maintaining social life for the better. This type of community service uses a face-to-face dialogue approach, Observation and Win-Win Solutions which the authors interpret using descriptively described words, which are meant as a series of explanations for the results of community service that have been carried out. The results of the service provide a participatory form of social development-based innovation where the innovation is a series of communities on the island of Penyengat Tanjungpinang. In addition, to support the innovation strategy of social development, it is necessary to improve the quality of human resources, or the community can play an active role from five sectors (infrastructure, health, culture, social and environment) which are the main focus in encouraging community-based social development innovation. It is hoped that with this social development innovation strategy, it can increase the independence of the people of Penyengat Island in making efforts to improve the welfare of the community to get a positive impact which has been implemented as a reference for social development innovations in Tanjungpinang City.